2020
DOI: 10.7717/peerj.8357
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes associated with multiple sclerosis based on gene expression data from peripheral blood mononuclear cells

Abstract: The aim of this study was to identify the potential key candidate genes of multiple sclerosis (MS) and uncover mechanisms in MS. We combined data from the microarray expression profile of three MS stages and performed bioinformatics analysis. Differentially expressed genes (DEGs) were identified among the distinct stages of MS and healthy controls, and a total of 349 shared DEGs were identified. Gene ontology (GO) and pathway enrichment analyses showed that the DEGs were significantly enriched in the biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…These results were accompanied by enrichment pathways in cell type specific genes, indicating the different etiological mechanisms in PLS1 + and PLS1 − gene sets and the potential clinical applications of intersubject variability in WMFC. Considering multiple sclerosis as a typical disorder with abnormalities in WM, we also determined the relationships between WMFC intersubject variabilities and differentially expressed genes in multiple sclerosis 53 . We found that WMFC intersubject variability was correlated with dysregulated gene expression ( r = –0.29, P moran = 0.0002; Supplementary Result 7 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results were accompanied by enrichment pathways in cell type specific genes, indicating the different etiological mechanisms in PLS1 + and PLS1 − gene sets and the potential clinical applications of intersubject variability in WMFC. Considering multiple sclerosis as a typical disorder with abnormalities in WM, we also determined the relationships between WMFC intersubject variabilities and differentially expressed genes in multiple sclerosis 53 . We found that WMFC intersubject variability was correlated with dysregulated gene expression ( r = –0.29, P moran = 0.0002; Supplementary Result 7 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, our analysis shows that hsa-miR-335-5p is the top ranked miRNA in the regulation of the black module. Since the black module consists mostly genes involved in inflammatory response, the upregulation of hsa-miR-335-5p is proposed to have inflammatory suppression effects [ 43 45 ]. More recently, hsa-miR-335-5p is shown to reduce inflammation via negative regulation of the TPX2-mediated AKT/GSK3β signaling pathway in a chronic rhinosinusitis mouse model [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, through a systems biology approach, researchers can generate gene and protein networks and identify genetic variants and novel molecules that heavily contribute to the pathogenesis of MS (73,74). A previous study by Shang et al (75), as an example, made use of such techniques and identified differentially expressed genes in MS, while pinpointing a number of genes heavily associated with the disease, including transcription factors (FOS, TP53, JUN and ATF3) and genes whose function was associated with the immune system (OAS2) and inflammation (IL8).…”
Section: Multiple Sclerosis and Computational Biologymentioning
confidence: 99%